Recovering Secrets From Prefix-Dependent Leakage - Ferradi Houda; Géraud Rémi; Guilley Sylvain; Naccache David; Tibouchi Mehdi (Journal of Mathematical Cryptology, 2020)
We discuss how to recover a secret bitstring given partial information obtained during a computation over that string, assuming the computation is a deterministic algorithm processing the secret bits sequentially. That abstract situation models certain types of side-channel attacks against discrete logarithm and RSA-based cryptosystems, where the adversary obtains information not on the secret exponent directly, but instead on the group or ring element that varies at each step of the exponentiation algorithm.